The Fund's Income Position for FY 2021 : Actual Outcome. (Policy Papers; Policy Paper ;, 2021)
This paper reports on the Fund's income position for FY 2021 following the closing of the Fund's accounts for the financial year and completion of the external audit. Overall FY 2021 net income amounted to SDR 4.8 billion or SDR 0.7 billion higher than estimated in April, mainly reflecting a larger than anticipated gain reported under IAS 19 (the accounting standard for employee benefits) and endowment returns exceeding earlier projections.